2005
DOI: 10.4049/jimmunol.174.6.3204
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of T Cell Ligands on Artificial APC Membranes Influences T Cell Activation and Protein Kinase C θ Translocation to the T Cell Plasma Membrane

Abstract: T cell activation is associated with active clustering of relevant molecules in membrane microdomains defined as the supramolecular activation cluster. The contact area between these regions on the surface of T cells and APC is defined as the immunological synapse. It has been recently shown that preclustering of MHC-peptide complexes in membrane microdomains on the APC surface affects the efficiency of immune synapse formation and the related T cell activation. Disruption of such clusters may reduce the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…In order to prepare artificial APC, we used the approach described by Albani et al for the identification of rare antigen-specific T cells in autoimmune disorders [34][35][36] with the following modifications. Our artificial APC consisted of a scaffold made of GM1-enriched liposomes, which anchor microdomains where mouse anti-human CD3 (clone UCHT1, isotype IgG1k; BD PharMingen, San Diego, CA, USA), CD28 (cloneCD28.2, isotype IgG1k; BD PharMingen) and LFA1 (clone 38, isotype IgG2a; Biodesign, Saco, Maine, USA) triggering mAb had been preclustered ( Figure 1A).…”
Section: Generation Of Artificial Antigen-presenting Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to prepare artificial APC, we used the approach described by Albani et al for the identification of rare antigen-specific T cells in autoimmune disorders [34][35][36] with the following modifications. Our artificial APC consisted of a scaffold made of GM1-enriched liposomes, which anchor microdomains where mouse anti-human CD3 (clone UCHT1, isotype IgG1k; BD PharMingen, San Diego, CA, USA), CD28 (cloneCD28.2, isotype IgG1k; BD PharMingen) and LFA1 (clone 38, isotype IgG2a; Biodesign, Saco, Maine, USA) triggering mAb had been preclustered ( Figure 1A).…”
Section: Generation Of Artificial Antigen-presenting Cellsmentioning
confidence: 99%
“…To this end, biotinylated anti-CD3, anti-CD28 and anti-LFA1 mAb were combined with biotinylated cholera toxin B (Sigma-Aldrich Inc.) in a 3:1 molar ratio for 5 min at room temperature, as previously described. 34 Subsequently, neutravidin (Pierce Biotechnology, Rockford, IL, USA) was added at a ratio of 1 mol per four biotinylated moieties. After 15 min of incubation at room temperature, the ganglioside GM1-enriched liposomes (kindly provided by Dompè Biotec Spa, L'Aquila, Italy) were added.…”
Section: Generation Of Artificial Antigen-presenting Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bead-based systems also have some drawbacks, including high cost of the beads, the labor-intensive process of removing the beads from the culture before infusion, and the inability of these beads to expand CD8 + T cells (21)(22)(23)(24). The artificial liposomes and exsomes show some potential for T-cell expansion, but the high cost, long-time procedure and biosafety should be considered for clinical therapy (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…62,63 In agreement, clustered pMHC molecules inserted in planar lipid bilayers exert enhanced T-cell activation as compared with uniformly-distributed MHC ligands. 64 A single-molecule-imaging analysis revealed that microclusters are relatively static, although their components are in a highly-dynamic state, moving in and out of the cluster. 65 TCR microclusters move independently toward the center of the IS and fuse to form large clusters: the interconnected large clusters become then immobilized at the center of the IS, and form the TCR-cSMAC.…”
Section: The New Conceptsmentioning
confidence: 99%